Antibiotics utilization review in a neonate intensive care unit of a public hospital in Surabaya - Felix Hidayat; Adji P. Setiadi; Eko Setiawan (Universitas Padjadjaran, 2019)
Antibiotic is one class of drugs that has been frequently used in the Neonatal Intensive Care Unit (NICU). The aim of this study was to identify the profile and to review the cost, appropriateness, and compatibility of antibiotics given to the patients in the NICU of one public hospital in Surabaya during November to December 2015. This was an observational prospective study using medical record as the main source of the data. All of information about eligible patients receiving antibiotics in the NICU was analysed descriptively. There were 32 patients involved in this study. The antibiotics utilization profile consisted of 25 single and 14 combination therapy. Ampicillin and ampicillin-gentamicin were found as the most frequently used in the single and combination therapy, consecutively. From all patients received antibiotics, there were 13 patients had been diagnosed with infections problem and only 2 patients (15.38%) received appropriate antibiotics therapy. The most frequently implemented mode of antibiotics changing strategy was de-escalation i.e. 44.44%. Based on the analysis of compatibility, it was found that there were lots of results of analysis classified as no-information. The average cost of antibiotics per patient was IDR 265,252 (range IDR 16,100 to IDR 2,091,500). There is a need to optimize the use of antibiotics in the NICU in order to minimize the risk of adverse outcomes especially the increased cost and risk of resistance.